Motor 'surround inhibition' is not correlated with activity in surround muscles. (10th May 2014) - Kassavetis, Panagiotis; Sadnicka, Anna; Saifee, Tabish A.; Belvisi, Daniele; van den Bos, Mehdi; Pareés, Isabel; Kojovic, Maja; Rothwell, John C.; Edwards, Mark J.
Abstract Surround inhibition (SI) is a neural process that has been extensively investigated in the sensory system and has been recently probed in the motor system. Muscle‐specific modulation of corticospinal excitability at the onset of an isolated finger movement has been assumed to reflect the presence of SI in the motor system. This study attempted to characterise this phenomenon in a large cohort of normal volunteers and investigate its relationship with muscle activity in the hand. Corticospinal excitability of the pathways projecting to three hand muscles [first dorsal interosseus (FDI), abductor pollicis brevis (APB) and abductor digiti minimi (ADM)] and electromyographic (EMG) activity of the same muscles were assessed in 31 healthy volunteers during an isolated index finger movement. In the agonist FDI muscle both corticospinal excitability and EMG activity were found to be increased at the onset of the movement (P < 0.001 and P < 0.001, respectively). On the contrary, in the surround ADM, there was dissociation between the corticospinal excitability (decreased: P < 0.001) and EMG activity (increased: P < 0.001). Cross‐correlation analysis of the EMG activity showed that neuronal signals driving the agonist and surround muscles are not synchronised when SI is present. The results suggest a distinctive origin of the neuronal signals driving the agonist and surround muscles. In addition, they indicate that cortical output might be simultaneously modulated by voluntary and non‐voluntary activity, generated in cortical and subcortical structures, respectively.